DANDELION OPTIMIZATION-BASED MODIFIED ULTRA SPARSE MATRIX CONVERTER FOR UNBALANCED AND HARMONIC GRID (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Variations in wind speed led to a non-constant power output from the wind energy conversion system (WECS). With wind energy penetration into utility grids increasing, there are challenges in the power quality of the electricity supply. Several existing techniques have been introduced; however, they are challenged by harmonics in wind power output from WECS and traditional matrix converters, which are inefficient due to their high switch count, low voltage transfer ratio, and sensitivity to changing conditions. In this research, a modified ultra-sparse matrix converter (MUSMC) has been proposed to improve the quality of wind power and feed the power to the grid. A modified ultra-sparse matrix converter configuration is designed for power transfer from the WECS to the grid. A dandelion closed-loop-based optimization (DLO) method is presented for injecting harmonically less electricity from wind power systems into the grid. The suggested DLO-based MUSMC system is designed to provide a voltage gain ranging from 0.8 to unity. The proposed system's performance is simulated in MATLAB/Simulink R2021a and tested while considering grid harmonics, an unbalanced grid, and changes in modulation schemes. According to the simulation findings, the suggested modular control approach with the MUSMC performs well under all three test situations, and the FFT analysis demonstrates the control strategy's superiority. This proposed methodology decreases the system's losses, size, and cost.
Keywords: Current space vector modulation method; Dandelion optimization; Doubly fed induction generator; Ultra-sparse matrix converter; Z-source network